التوزع الفصلي للهطول في المنطقة الداخلية الوسطى في سورية - سليمان أمين (Latakia University Journal -Engineering Sciences Series, 2018)
Knowing the temporal distribution of precipitation greatly helps in management and exploitation of water resources, especially in the agricultural sector. In order to study the seasonal distribution of precipitation in the central region of Syria, daily precipitation data were obtained from the official authorities for six meteorological stations. Due to the large number of data, it was necessary to use a computer program especially designed for this purpose, to form the seasonal precipitation series by adopting three type of divisions, normal seasons, traditional division of seasons, and dividing winter season into “ the Forty winter days” and “Fifty winter days”, and the Saudats period. According to time series it was found the precipitation season approximately starts on October 16, ends on May 6, and the mid-season on January 22. Based on the seasonal series of precipitation, it was found that the precipitation in Autumn is 19% of the annual precipitation according to the normal division and 30.2% according to the traditional division. The precipitation in Winter is about 54% of the annual precipitation according to the normal and traditional seasons divisions. Precipitation in Spring is 16.1% of the annual precipitation according to the traditional division, and about 26% according to the normal division, the precipitation rate in Summer does not exceed 1% of the annual precipitation according to the normal and traditional division. The relative frequency of the mid-October fall is 69.4%, and the smallest relative frequency is about 8.7% for “ The Cross fall”. The frequency of 17th March and fourth April falls are about 53%. إن معرفة التوزع الزمني للهطول يساعد إلى حد بعيد في إدارة واستثمار الموارد المائية على الأخص في المجال الزراعي. ولدراسة التوزع الفصلي للهطول في المنطقة الوسطى من سورية تم الحصول من الجهات الرسمية على بيانات الهطول اليومية في ست محطات للأرصاد الجوية. ونظراً لعدد البيانات الكبير كان لا بد من الاستعانة ببرنامج حاسوبي صُمم خصيصاً لهذا الغرض، كانت الغاية منه تشكيل السلاسل الفصلية للهطول حسب تقسيمات ثلاث، تقسيمي الفصول العادي والتراثي، وتقسيم فصل الشتاء إلى أربعين وخمسين الشتاء والسعودات. وبناء على السلاسل الزمنية لتواريخ بداية ونهاية موسم الهطول، ومنتصفه، تبيّن أن موسم الهطول يبدأ وسطياً في 16 تشرين أول، وينتهي وسطياً في 6 أيار، وإن منتصف الموسم وسطياً هو في 22 كانون الثاني. كما تبين من دراسة السلاسل الفصلية للهطول أن نسبة الهطول في فصل الخريف 19% من الهطول السنوي حسب التقسيم العادي و30.2% حسب التقسيم التراثي، ونسبة الهطول في فصل الشتاء حوالي 54% من الهطول السنوي حسب التقسيم العادي والتراثي للفصول، ونسبة الهطول في فصل الربيع 16.1% من الهطول السنوي حسب التقسيم التراثي، وحوالي26% حسب التقسيم العادي، وأن نسبة الهطول في فصل الصيف لا تتجاوز 1% من الهطول السنوي حسب التقسيم العادي والتراثي. وإن التكرار النسبي لرية النصف من تشرين أول حوالي 69.4%، وأقل تكرار نسبي هو لرية الصليب حوالي8.7%، وإن التكرار النسبي لريتي الـ17 من آذار والرابع من نيسان حوالي 53%.